Neurological outcomes in neonates treated with therapeutic hypothermia: challenges in a developing country - Rita Farias Oliveira; Lucia Helena Wagner; Alexandre Sousa da Silva; Maura Calixto Cecherelli de Rodrigues; Glenda Corrêa Borges de Lacerda (Arquivos de Neuro-Psiquiatria)
Background Hypoxic-ischemic encephalopathy (HIE) affects 1.5 newborns per 1 thousand term live births. Therapeutic hypothermia (TH) does not prevent all adverse outcomes. The experience with TH is still limited in Latin America. In Rio de Janeiro, Hospital Universitário Pedro Ernesto treats neonates with HIE since 2017 using the servo-controlled system.